Muraqqaʻ-i suḵẖan : Ḥaidarābād ke paccīs mumtāz shuʻarā-yi daur-i Āṣafiyah kā bā taṣvīr taẕkirah - Zore, Muhiuddin Qadri, 1905-1962 (SAMP early 20th-century Indian books project ;, 1935)
Collective biography of twenty five eminent Urdu poets from Hyderabad, India; includes selection of their poems.